Lower six students` preferred mode of feedback for essay revision - Govindasamy, Potchelvi N.; Tan, Bee Hoon; Yong, Mei Fung (Malaysian English Language Teaching Association, 2013)
ESL students value feedback to their essay drafts. Through feedback and by doing multiple revisions, they learn to develop and express complex ideas clearly and effectively. Accordingly, feedback is seen as a way to improve the communicative effectiveness of a given written piece by correcting and guiding students so that their ideas are effectively communicated to the reader.This study determined the students’ preference towards feedback type during essay revision. The quasi-experimental study used the counter-balanced research design.For comparison,the students in this study were exposed to two different treatments, teacher-written feedback and online-automated feedback for twelve weeks.The results revealed that the students preferred teacher-written feedback to online -automated feedback although both the experimental groups showed improvement in their essay writing based on both modes of feedback.